(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An outbreak of larvae of a devastating moth was observed in an eggplant(Solanum melongena L.) field at Elselate Scheme, Khartoum State, Sudan, during April2007, with symptoms such as foliage-mining, leaf defoliation and fruit burrowing underthe calyx and through the fruit skin. The pest incidence was sufficient to causesignificant yield loss in most fields. Larvae of the pest were collected and reared in thelaboratory in Shambat Research Station. Adult moths of the order Lepidoptera emerged.Specimens of the pest and photographs of the symptoms were sent to the FinnishMuseum of Natural History, University of Helsinki, Finland, for identification. The pestwas identified as Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) which hadalready been reported in Sudan as a pest on potato and tomato.